Osmotic and Hemodynamic Effects of Hypertonic Glucose During Hemodialysis. Issue 6 (November 2017) - Schneditz, Daniel; Niemczyk, Stanisław; Sauseng, Notburga; Bachler, Isolde; Zierler, Edda; Lackner, Helmut Karl; Hafner-Giessauf, Hildegard
Abstract : It was the purpose to quantify the hemodynamic effects of a bolus of hypertonic glucose injected into the extracorporeal system in a group of stable and nondiabetic patients during hemodialysis (HD). Glucose and electrolytes were measured in frequent intervals. Arterial blood pressures and heart rates were continuously recorded by noninvasive vascular unloading technique. Beat-to-beat stroke volume, cardiac output, and total peripheral resistance were determined by Modelflow method. Relative blood volumes were continuously measured by ultrasonic and optical means. Eight patients were studied in two treatments. Although arterial pressures and heart rates remained stable, stroke volume and cardiac output transiently increased above (19.2 ± 12.3%) and total peripheral resistance dropped below baseline (18.2 ± 8.6%) by a comparable magnitude. Relative blood volume transiently increased above baseline at 100% (104.9 ± 1.0%). Glucose concentrations were significantly related to relative blood volumes ( r 2 = 0.86, p < 0.001). In spite of a substantial increase in blood volume, a bolus of hypertonic glucose does not increase arterial pressures in nondiabetic patients because of concomitant vasodilatation. The relative increase in blood volume quantified by noninvasive HD technology follows the course of glucose and could be used as a surrogate to characterize patients with regard to their glucose metabolism during HD.